Putting Equity Back in Reverse Mortgages: Helping Seniors Retire with Dignity - Helman, Andrew (Maine Policy Review, 2010)
Policymakers can help some seniors age in place through policies to strengthen private-sector reverse mortgages. In reverse mortgages, individuals who may be “house rich but cash poor” can use their home’s equity to receive regular income or get money through a credit line. Andrew Helman argues that state legislatures can help seniors avoid the “tricks and traps” of reverse mortgages by establishing programs in which lenders who agree to play by rules that ensure the safety and security of such mortgages are placed on a “preferred” list for seniors seeking a loan. He observes that laying the groundwork now can help a larger group of seniors age with dignity.
Keywords: Maine; reverse mortgages; elders